A Miniature Raspberry Shaped UWB Monopole Antenna based on Microwave Imaging Scanning Technique for Kidney Stone Early Detection - Jamall Abdullah Al-Gburi, Ahmed; Ibrahim , IM; Z. , Zakaria (International Journal of Psychosocial Rehabilitation, 2020)
A small monople antenna is presented and experimentally discussed for kidney stone early detection at an ultra wide band frequency range (3-11) GHz. The malformation of the kidney can be specified through an ultrasound machine. The kidneys may have an atomic alanomalya-like kidney malformation, which in turn develops in its location and semblance. Kidney malformation may as well grow because of the creation of stones, inherent defects, clogging of urine, etc. For surgical operations, it is extremely necessary to locate the precise position of the stone in the kidney. The ultra-sound machine is high-inoizing radiation that effects the human body; micro-wave imaging can be a perfect substitute. A UWB monopole antenna scanning technique authorized to recognize the right and accurate position of stone in the kidney. This antenna has a very low profile, simple structure, is easy to manufacture, and is light weight, hence producing good results in radiation characteristics. High gain of 5 dB at frequency 11GHz. The substrate is based on the RT Rogers 5880 with dielectric constant of 2.2. With overall dimensions of 17.5 mm x17.5 mm x 0.8 mm. Anauthentic verification system will be developed for the purpose of creating antenna response level overt issues that could represent the human body. The water is selected to be used in the practical measurement because it has nearly identical density characteristics as the human body. In the interest of demonstrating stone existence in a symmetrical medium, a small calcium stone is adjusted to measure the anomaly.